O mundo interno nas páginas infantis de Clarice Lispector: história, literatura e criação cultural - Silva, Lohanne Gracielle (2020)
In the late 1960s and 1970s, writer Clarice Lispector, known for an extensive work produced for adults, wrote five children's books: The mystery of the thinking rabbit, The woman who killed the fish, Laura's intimate life, Almost real and How the stars were born: twelve Brazilian legends. At the same time that she wrote for newspapers and books for adults, she dedicated herself to writing children's books. This thesis has as its source and object of research the narratives aimed at children, with the intention of analyzing literary writing for children and its meaning from a historical perspective. It is interesting to understand the representations that these works produce about the internal world of children, understanding their production immersed in a complex cultural context. In the pages of these works, it is possible to observe, through words and images, constructions about childhood in which themes such as death, revenge, love, longing, desire and fear are central to the stories told, showing the ambivalent and complex character of human existence. We can see the problematization of the "inside", in which subjectivities become the center of the narrative. The psychological universe, already present in the works of Clarice Lispector for adults, takes the pages of books aimed at children, allowing to situate these stories as pieces of a single puzzle that composes her work and marks her artistic style.